STUDY ON THE DEVELOPMENT OF FISHERIES FACILITIES AND INFRASTRUCTURE IN THE EAST BARAN VILLAGE MERAL DISTRICT KARIMUN REGENCYRIAU ISLANDS PROVINCE - Maisa Dela Putri; Jonny Zain; Syaifuddin Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract                     This research was conducted from April to May 2019 aims to determining the type, size and capacity of fishery facilities needed by fishermen inEast Baran Village  with the method used in the form of a survey method. The results showed that the infrastructure of fisheries that exist in the East Baran Village is The Fish Landing who have the means as piers, port pool, parking lots, warehouses, canteen and UPT Fisheries, in addition to the means of support fisheries that exist in the East Baran Village include factory ice, and gas stations that are outside TPI.To support all fishery activities in the TPI of East Baran Village, the length of the unloading pier with a size of 6.09785 meters and the length of the mooring dock is 32.224375 meters.For the amount of fishing needs in TPIEast Baran Village, it is divided into 57.5 liters of diesel fuel, 1412.5 kg of ice and 1025,167 liters of fresh water in one day. Keywords: Facilities, Longline, Fisherman Opinion